(Study on bleaching and deodoration of squalene by the mixture of activated carbon and bentonite (1:8)). - Achmad Moestafa Achmad Moestafa; Hendarti -; Tiurlan F.Hutajulu; Ali Sudirman (Balai Besar Industri Agro, 1995)
Squalene which was extracted from shark liver oil (Centrophorus atromarginatus) should be purified before it can be used as raw material in industry.Raw squlene has dark yellow in colour and has an unpleasant odour, while a commercial squlene is an odourless clear liquid.To meet the requirement an experiment had been carried out by treating the raw squlene by mean of an absorbent which consist of a mixture of activated carbon and bentonite in 1:8 ratio.An acceptable squalene was found when raw squalene was treated with 2.0% adsorbent at 105-110 degree C for 120 minutes.The product was an odourless liquid.